Compensatory eye and head movements of patients with homonymous hemianopia in the naturalistic setting of a driving simulation - Bahnemann, Markus; Hamel, Johanna; De Beukelaer, Sophie; Ohl, Sven; Kehrer, Stefanie; Audebert, Heinrich; Kraft, Antje; Brandt, Stephan A. (Journal of neurology, 2015)
Homonymous hemianopia (HH) is a frequent deficit resulting from lesions to post-chiasmal brain structures with a significant negative impact on activities of daily living. To address the question how patients with HH may compensate their visual field defect in a naturalistic environment, we performed a driving simulation experiment and quantitatively analyzed both eye and head movements using a head-mounted pupil camera. 14 patients with HH and 14 matched healthy control subjects participated in the study. Based on the detection performance of dynamically moving obstacles, which appeared unexpectedly along the sides of the road track, we divided the patient group into a high- and a low-performance group. Then, we compared parameters of eye and head movements between the two patient groups and the matched healthy control group to identify those which mediate successful detection of potentially hazardous objects. Differences in detection rates could not be explained by demographic variables or the extent of the visual field defect. Instead, high performance of patients with HH in the naturalistic setting of our driving simulation depended on an adapted visual exploratory behavior characterized by a relative increase in the amplitude and a corresponding increase in the peak velocity of saccades, widening horizontally the distribution of eye movements, and by a shift of the overall distribution of saccades into the blind hemifield. The result of the group comparison analyses was confirmed by a subsequent stepwise regression analysis which identified the horizontal spread of eye movements as single factor predicting the detection of hazardous objects.